Impact of air temperature on occurrence of bath-related cardiac arrest. Issue 37 (17th September 2021) - Hiraki, Katsushige; Irie, Jin; Nomura, Osamu; Machino, Hiromi; Yaguchi, Shinya; Ishizawa, Yoshiya; Soma, Yuki; Hanada, Hiroyuki
Abstract : Abstract: The mortality of the bath-related cardiac arrest (BRCA) is extremely high. While air temperature is reported to be associated with the BRCA occurrence, it is unclear whether daily minimum temperatures or the difference between maximum and minimum air temperatures influences BRCA occurrence the most. A retrospective cohort study of adult patients was conducted between January 2015 and February 2020 at Hirosaki University Hospital Emergency Department. The following data were collected: age, sex, day of cardiac arrest event, location of the event, initial cardiac rhythm, presence of return of spontaneous circulation, and overall mortality (status at 1 month after cardiac arrest event). Based on the day of the event and the location in which the event occurred, daily minimum and maximum temperatures were obtained from the Japan Meteorological Agency database. A total of 215 eligible cardiac arrest cases were identified, including 25 cases of BRCA. Comparing BRCA and non-BRCA, initial shockable cardiac rhythm (4.0% vs 44.7%), presence of return of spontaneous circulation (8.0% vs 34.7%), and overall mortality (96.0% vs 71.6%) differed significantly ( P  < .05 each). Daily minimum and maximum temperatures showed no significant relationships with BRCA or non-BRCA. Daily minimum temperature was a risk factor of BRCA occurrence after adjusting for age and temperature difference (risk ratio, 0.937; 95% confidence interval, 0.882–0.995). Daily minimum temperature represents a potential risk factor for BRCA occurrence. Abstract : Supplemental Digital Content is available in the text